2003
DOI: 10.1152/ajpcell.00013.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fibroblast proliferation in cardiac myocyte cultures by surface microtopography

Abstract: Cardiac myocyte cultures usually require pharmacological intervention to prevent overproliferation of contaminating nonmyocytes. Our aim is to prevent excessive fibroblast cell proliferation without the use of cytostatins. We have produced a silicone surface with 10-microm vertical projections that we term "pegs," to which over 80% of rat neonatal cardiac fibroblasts attach within 48 h after plating. There was a 50% decrease in cell proliferation by 5 days of culture compared with flat membranes (P < 0.001) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 38 publications
5
91
0
Order By: Relevance
“…Micropegs on a 2D surface decrease proliferation of fibroblasts compared to flat surfaces. 4 In addition, this was correlated with a significant decrease in Cyclin D1 expression, demonstrating that cell proliferation was affected at the level of G1/S cell cycle transition. 4 Further, this effect was dependent on local micropeg-cell interactions and was regulated by contractile mechanics.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Micropegs on a 2D surface decrease proliferation of fibroblasts compared to flat surfaces. 4 In addition, this was correlated with a significant decrease in Cyclin D1 expression, demonstrating that cell proliferation was affected at the level of G1/S cell cycle transition. 4 Further, this effect was dependent on local micropeg-cell interactions and was regulated by contractile mechanics.…”
mentioning
confidence: 94%
“…In the last several years, mechanical, topographical, and geometrical cues have been shown to modulate cellular morphology and behavior in twodimensional (2D) and three-dimensional (3D) systems. [4][5][6][7][8][9][10][11][12] However, the potential to control fibroblast behavior and ECM synthesis using discrete microtopographical cues has not been fully explored. This knowledge could provide a better understanding of the role of topography in matrix remodeling, with the potential to enhance regenerative therapies.…”
mentioning
confidence: 99%
“…Knowledge of these interactions is crucial to the understanding of many fundamental biological questions and to the design of medical devices. Tissue engineering is an example where control of these interactions is essential to the creation of functional engineered-tissues [1][2][3][4][5][6]. The performance of many implantable medical devices is also dependent on the desired device-tissue response [7].…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the PTEN inhibition study, a specific PTEN inhibitor SF1670 originally used in neutrophils (15) and was confirmed here in cardiomyocytes. ANG II increased PIP 2 , which was significantly reduced by SF1670 treatment while also dramatically increasing PIP 3 (Fig. 3, A and B).…”
mentioning
confidence: 84%